Riverine people of Borneo : everyday political ecology of ‘lanting’ community in Sintang, West Kalimantan - Lubis, Mira S.; Susanto, Dalhar; Harjoko, Triatno Y. (Penerbit Universiti Kebangsaan Malaysia, 2021)
In the cities of Global South, riverbank settlements is often generalized, even stigmatized as slums. It also happened in the cities of Borneo, the largest island in Maritime Southeast Asia, which historically are deeply rooted in riverine culture. This study figures out the everyday political ecology of the inhabitants of the Kapuas River settlements in the form of ‘lanting’ or raft houses, in the midst of rapid urban development and environmental changes, which reflects their efforts in defending their existence as part of the urban society. Spatial ethnographic approach supported with observation and in-depth interviews were used to reveal the everyday political ecology of the lanting’s inhabitants in Sintang, the city chosen for this study. Converting the events into tactic-strategy approach, this study reveals the important meanings behind the daily activities of the lanting inhabitants which reflects the significant influence of people’s thoughts and actions in the production and reproduction of their living space. The results of this study confirm that the dwelling practice of the lanting community is not merely something caused by economic limitations. More than that, it is deeply integrated with urban economic activities and makes significant contributions to urban-rural socio-economic linkages based on dendritic river networks.